Microstructure Analysis, Optical, and Electrical Transport Properties of NiAl2O4/Al2O3 Nanocomposite Powder. Issue 22 (8th September 2022) - Dhara, Arup; Sain, Sumanta; Ray, Apurba; Das, Sachindranath; Kumar Pradhan, Swapan
Abstract : The microstructure characterization, optical properties, electrical transport, and dielectric properties of the thermally stable NiAl2 O4 /Al2 O3 nanocomposite powder sample synthesized by the mechanochemical‐assisted solid‐state reaction from the equimolar mixture of NiO and Al2 O3 powders are reported. Rietveld refinement, selected‐area electron diffraction pattern, and Fourier‐transform infrared spectrum analyses confirm the formation of a NiAl2 O4 spinel phase with a minor Al2 O3 phase in the as‐synthesized powder. Transmission electron microscope images reveal the particle size of the powder sample, ≈26 nm. Raman spectrum reveals the presence of NiAl2 O4 normal spinel as a major phase in the sample. The temperature and frequency dependence of the dielectric constants of the NiAl2 O4 /Al2 O3 nanocomposite are explained by Koop's phenomenological theory. The electric modulus approach is used to analyze the electrical transport and dielectric relaxation of NiAl2 O4 /Al2 O3 at different temperatures. The electric modulus plot with elevated temperature shows a dielectric loss peak and reflects interesting information on the grains and grain boundaries of the material with varying temperatures. Abstract : The modulus spectroscopy result of consolidated bulk NiAl2 O4 /Al2 O3 nanocomposite suggests the presence of two relaxation processes in the sample. Enhanced grain boundary contributions to the impedance of the nanocomposite with increased temperature are prominently observed in the modulus plots.